PREMEDICATION PROTOCOLS IN DENTAL PRACTICE IN ALLERGIC PATIENTS. - Angelina Kisselova; Adriana Krasteva; Assya Krasteva (Peytchinski Publishing, 2011)
The problem with choosing a suitable pre-medication protocols before local anesthesia in dentistry in allergic patients is always discussed, as in the dental practice different schemes are already proven (3,5). The propose of this communication is to share the experience on those pre-medication schemes in allergic patients during and outside pollen season.